Contrasting diversity patterns and community assembly mechanisms of bacterioplankton among different aquatic habitats in Lake Taihu, a large eutrophic shallow lake in China. (15th December 2022) - Bai, Chengrong; Gao, Guang; Tang, Xiangming; Shao, Keqiang; Hu, Yang; Xia, Jiangbao; Liu, Jingtao
Abstract: Eutrophication leads to the degradation of lake habitat types from macrophyte-dominated habitats (MDH) to algae-dominated habitats (ADH), which is a common environmental problem faced by many lakes. However, the variations in diversities and community assembly processes of bacterioplankton in the process of lake eutrophication have not been thoroughly elucidated. Here, we contrasted bacterial diversity patterns and processes of community assembly among ADH, MDH, and other habitats (OH) of Lake Taihu, a large shallow eutrophic lake in China with strong wind-induced disturbances. We found that the bacterial diversity patterns and potential functions between ADH and MDH were significantly different. Moreover, the contributions of purely environmental variables to the bacterial diversity patterns of all habitat types were much higher than those of spatial variables. However, the relative importance of stochasticity in the bacterial community assembly of each habitat type was much higher than that of determinism. Intriguingly, 'undominated' stochastic processes shape the diversity patterns of bacterioplankton in ADH, MDH, and OH of Lake Taihu. These findings demonstrate that the degradation of lake habitats caused by eutrophication can profoundly change the diversity and potential function patterns of the bacterioplankton community in lake ecosystems. Although the distinct diversity patterns of the bacterioplankton among the different aquatic habitats in Lake Taihu can be affected by deterministic processes (local environmental variables), they were dominated by stochastic processes (drift). Our study confirms that strong, disordered, wind-induced disturbances in shallow lakes could lead to strong hydrologic mixing, thus increasing the randomness of bacterial community assembly in each habitat. Graphical abstract: Image 1 Highlights: Bacterial diversity patterns between the ADH and MDH are significantly different. Bacterial diversity patterns in Lake Taihu were dominated by stochastic processes. Wind-induced disturbance increases the randomness dispersal of bacterioplankton.